The mind of Thucydides - Romilly, Jacqueline de (Cornell University Press, 2012)
First published in France in 1956 and now available in English for the first time, this narratological analysis of Thucydides's ""History of the Peloponnesian War"" highlights the power and sophistication of the Greek historian's rhetoric.
Keywords: Thucydides. -- History of the Peloponnesian War.; History of the Peloponnesian War (Thucydides); HISTORY -- Ancient -- Greece.